solve for in y of the other variables

You are given the following equation: y + u = x <==> x = y + u

Looking at the equation, we see that it is solved for x in terms of the other variables, y and u, since it basically states that x is equal to the sum of y and u.

To solve this equation for y in terms of the other variables, x and u, we need to isolate the y variable to one side of the equation by moving all other variables to the other side of the equation.

y + u = x to solve for y, subtract u from both sides of the equation

y + u **- u** = x
**- u**

y + 0 = x - u

**y = x - u**

## Comments

thank you, for you help Tamara.